An Early Mediaeval Cemetery at Sowinki (Mosina Commune, Poznań Voivodeship) – Anthropological and Paleodemographic Analysis - Kozak, Jerzy (Anthropological Review, 1996)
This paper presents the results of anthropological examinations (morphological characteristics and paleodemographic analysis) of human bone remains (121 individuals) discovered in the cemetery at Sowinki (10th/11th century).